Pengaruh Model Pembelajaran MIKIR Berbasis Storytelling terhadap Keterampilan Berkolaborasi Siswa Kelas V - Muhammad Fathul Fuadi; Syamsuyurnita Syamsuyurnita; Dewi Kesuma Nasution; Mandra Saragih (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This study aims to determine the effect of using storytelling-based experience, interaction, communication, and reflection (thinking) learning models on the collaboration skills of fifth grade students in the Learning Studio, North Gombak, Malaysia. The category of this research is Pre-Experimental research using the One group Pretest design. t-Posttest Design. The sample of this study was the fifth grade students of the North Gombak Learning Studio, Malaysia, totaling 8 students. The data were collected using tests and observations. Meanwhile, the research data were analyzed descriptively and inferentially with the t test, based on the average posttest results obtained. the posttest average results of students' collaborative skills after the implementation of the storytelling-based thinking learning model was greater than the average pretest result before the implementation of the storytelling-based thinking learning model, the average pretest obtained before the implementation of the storytelling-based thinking learning model was 63.75 after being given activities with the treatment of the storytelling-based Thinking learning model so that the posttest average score was 85.00. It can be concluded that the form of storytelling-based Thinking learning that is applied to Indonesian language learning has an effect on the collaboration skills of class V students at the Learning Studio, North Gombak, Malaysia